Chronic Opiate Use in Pregnancy and Newborn Head Circumference - Visconti, Kevin C.; Hennessy, Kerry C.; Towers, Craig V.; Howard, Bobby C. (American Journal of Perinatology, 2015)
Objective The aim of the study is to evaluate whether chronic opiate use in pregnancy affects newborn head circumference (HC).Study Design All newborns from January 1, 2010, to June 30, 2012, admitted to the neonatal intensive care unit for treatment of neonatal abstinence syndrome were prospectively collected. The demographic, obstetrical, neonatal, and perinatal ultrasound data were retrospectively obtained. A gestational age-matched control was used for comparison purposes.Results Of 332 neonates admitted for the treatment of neonatal abstinence syndrome, 98 (29.5%) had a HC ≤ 10th percentile for gestational age that was significantly increased when compared with controls (p < 0.001). Of these 98, 25 had a HC ≤ 3rd percentile. Of the case population, 141 had an ultrasound in the perinatal unit within 10 days of birth. A HC < 5th percentile was found in 38.3% of cases of which 74% were ≤ 10th percentile postdelivery. The ultrasound femur and humerus length measurements were also < 5th percentile in 36.2 and 28.9%, respectively.Conclusion Chronic opiate use in pregnancy appears to increase the risk for a HC ≤ 10th percentile and ≤ 3rd percentile when compared with controls. From ultrasound findings, femur and humerus lengths also appear to be shortened suggesting a possible effect on bone growth.
Keywords: opiates; neonatal abstinence syndrome; newborn head circumference; prenatal substance abuse